Nurse's actions towards the prevention of cervical cancer in Primary Care (Research, Society and Development, 2021)
The objective of the research was to investigate the actions to prevent cervical cancer developed by nurses in the context of primary care. This is an exploratory field research, with a qualitative approach, in which 10 nurses from the Family Health Strategy (ESF) were interviewed during the month of January 2021 from a municipality in the interior of Paraíba, through a semi-structured script. Data were analyzed using Bardin's content analysis technique. The research was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba - CEP/CCS under the opinion 4.473.220, CAAE No. 40327520.7.0000.5188. The material analyzed generated two major categories: 1. Actions to prevent cervical cancer; 2. Adherence of women to preventive examination: strategies, difficulties and evaluation mechanism. The strategies mentioned to facilitate adherence to Pap smears refer to information and awareness regarding the test in educational activities, conversation circles and active search for women. The nurses highlighted difficulties in the adherence of women to the Pap smear, mainly related to the opposition of the spouse, shame, shame and prejudice.